Pengaruh Corporate Social Responbility, Struktur Modal, Enterprise Risk Management dan Ukuran Perusahaan terhadap Nilai Perusahaan - Irdawati Irdawati; Dirvi Surya Abbas; Imam Hidayat; Daniel Rahandri (FEB Universitas Maritim Semarang, 2022)
The purpose of this study was to determine the effect of corporate social responsibility, capital structure, enterprise risk management and firm size on firm value in various industrial sector companies listed on the Indonesia Stock Exchange. The research time period used is 5 years, namely the 2017-2021 period. The population of this study includes all companies listed on the Indonesia Stock Exchange for the period 2017-2021. The sampling technique used purposive sampling technique. Based on the predetermined criteria obtained 12 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis using the eviews 10 data processing program. The results showed that corporate social responsibility, enterprise risk management and firm size had an effect on firm value, while capital structure had no effect on firm value.